Juridical Review of Practice Permit Arrangements for Foreign Doctors in View of Health Law Number 17 of 2023 Jo Regulation of the Minister of Health Number 35 of 2022 and the Benefits of the Presence of Foreign Doctors for the People of Indonesia - Maulani, Alfira Kafi; Suherman Sewu, Pan Lindawaty; Octora, Rahel; Septina Basani, Christin (Universitas Ekasakti, 2024)
Competency evaluation is crucial components in the acceptance of foreign doctors in Indonesia, foreign doctor will be assessed for their ability and quality to help the improvement of health services standard in Indonesia. Many Indonesian citizen seeking medical treatment abroad and caused the country losing Rp.165 tillion, which may be due to the populace’s preference for services provided by hospitals overseas. Law are established to fulfill 3 principles; justice, benefits, and certainty. Regulation regarding foreign doctor practicing in Indonesia fulfills the principle of benefit in accordance with Article 2 letter c of Law Number 17 of 2023 concerning Health Law, which states that the principle of benefit in health development must provide the greatest benefit for humanity and a healthy life for every citizen. The method used in this research is normative juridical research with an approach through legislation and examination of norms and rules applicable in Indonesia.vThe government has made quite a lot of regulations governing the utilization of foreign healthcare workers. However it would be even better if the regulations itself could be harmonized and have many benefits to increase the quality of health services in Indonesia.